2015
DOI: 10.1080/00224499.2015.1015714
|View full text |Cite
|
Sign up to set email alerts
|

Inferences About Sexual Orientation: The Roles of Stereotypes, Faces, and The Gaydar Myth

Abstract: In the present work, we investigate the pop cultural idea that people have a sixth sense, called “gaydar,” to detect who is gay. We propose that “gaydar” is an alternate label for using stereotypes to infer orientation (e.g., inferring that fashionable men are gay). Another account, however, argues that people possess a facial perception process that enables them to identify sexual orientation from facial structure (Rule et al., 2008). We report five experiments testing these accounts. Participants made gay-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 68 publications
5
56
0
2
Order By: Relevance
“…As reported in Cox et al (2016), we found a quality confound in two stimulus sets collected in an attempt to replicate and extend some of Rule et al's (2008) work on perceiving orientation from the face (i.e., "face-based gaydar"). We discovered a natural confound, such that gay men's and lesbian women's pictures were of higher quality than those of their straight counterparts.…”
Section: Internal Validity Problems In Past Face-based Gaydar Researchmentioning
confidence: 56%
See 2 more Smart Citations
“…As reported in Cox et al (2016), we found a quality confound in two stimulus sets collected in an attempt to replicate and extend some of Rule et al's (2008) work on perceiving orientation from the face (i.e., "face-based gaydar"). We discovered a natural confound, such that gay men's and lesbian women's pictures were of higher quality than those of their straight counterparts.…”
Section: Internal Validity Problems In Past Face-based Gaydar Researchmentioning
confidence: 56%
“…In fact, as reviewed extensively by Rule and colleagues (2016) in reply to our recent article (Cox et al, 2016), several researchers claim that people's snap judgments about sexual orientation are largely accurate (e.g., Gaudio, 1994;Johnson, Gill, Reichman, & Tassinary, 2007;Rieger, Linsenmeier, Gygax, Garcia, & Bailey, 2010;Rule, Ambady, Adams, & Macrae, 2008). We argued that the conclusions of this past work were misleading and incorrect, based on (a) a methodological confound we serendipitously uncovered and (b) a fundamental flaw in the reasoning and design of the past work.…”
Section: Inaccuracy Of Gaydarmentioning
confidence: 68%
See 1 more Smart Citation
“…3 An anonymous reviewer asked whether we had collected information on the relationship between MP and a measure of unintentional bias. Because our lab was conducting a large-scale project that involved the Black/White pleasant/unpleasant IAT, a measure of unintentional race bias, we had the opportunity to assess, in a large sample of college student participants (N = 963), the relationship between the Black version of the MP scale and the race evaluative IAT (Cox, 2015). Further supporting our argument that the motivation to express prejudice scale measures a construct distinct from those tapped by other measures, it had a near-zero correlation with the race evaluative IAT (r = .060).…”
Section: Predictive Validitymentioning
confidence: 99%
“…Many have argued that people endorse stereotypes, including physical appearance stereotypes, because they hold negative attitudes toward minority groups (e.g., racial and sexual minorities) (13)(14)(15)(16) and because stereotypes can be used to justify the current structure of a society (17)(18)(19)(20). Conservatives often report more negative attitudes toward minority groups than liberals do (21,22), and are also more likely to endorse maintaining the current structure of a society (4,23).…”
mentioning
confidence: 99%